Stigma without Sanctions: The (Lack of) Impact of Private School Vouchers on Student Achievement - Bowen, Daniel H.; Trivitt, Julie R. (Education Policy Analysis Archives, 2014)
Under the Florida A+ Accountability Program, Florida’s schools are graded based on student performance on the Florida Comprehensive Assessment Test. Previously, when schools would earn their second failing grade within four years, students assigned to these schools were offered school vouchers which parents and guardians could use to transfer students to a private or another traditional public school. In January of 2006 the Florida Supreme Court declared that private school voucher component of the Florida A+ Accountability Program was unconstitutional, eliminating the threat of having these students and funds leaving to attend private schools. This exogenous shock allows us to test whether private voucher threats and the funding tied to these students led to increases in student achievement. We find no evidence that the private school voucher threats drive academic improvement beyond what is seen in schools when this private school voucher threat is removed.